Java 11 in 7 days - Karanie, Gulaam (Packt, 2019)
"Java was designed to be easy to use and is therefore easier to write, compile, debug, and learn than any other programming languages. You've been hearing people talk about Java and you want to get involved with the latest version so you don't risk getting left behind. If you can skip Netflix for a week, you will be able to learn this amazing new language that can save your time and money. This course is the perfect guide for you as it asks for just 30 minutes a day for 7 days. You will learn how to code in Java by following unique and intuitive examples. You will understand all the Java keywords, operators, statements, and expressions you'll need to fully understand how to code efficiently. By the end of this course, you will have learned everything you need to know to code profitable projects in Java and, of course, have fun whilst doing it."--Resource description page